Securing Enterprise AI: Protecting Sensitive Data in the Age of ChatGPT - Ravi Sastry Kadali (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the critical challenge of balancing innovation with data privacy as enterprises increasingly adopt AI chatbots and language models like ChatGPT. It examines the current landscape of enterprise AI integration, highlighting both the enthusiasm for these technologies and the primary concern of sensitive data exposure. Through case studies in the financial and healthcare sectors, the article illustrates pioneering approaches to secure AI implementation, including developing "AI sanitization layers" and "context-aware AI interactions." Key enterprise safeguards such as pre-processing filters, real-time monitoring, and secure API endpoints are discussed. The article also delves into future directions for secure AI integration, introducing concepts like "privacy-first AI integration" and specialized middleware for data sanitization. By presenting a comprehensive overview of the challenges, current solutions, and prospects, this article provides valuable insights for organizations seeking to harness the power of AI while maintaining robust data protection measures.